Developing Students’ Writing Skill through Peer and Teacher Correction: An Action Research - Sapkota, Ashok (Journal of NELTA, 2013)
Writing is a form of an art and integral part of language learning. The present study concerns with development of writing skills through peer and teacher correction technique. As an action research in nature, the research aimed to test the progress of the students while writing an essay. After the analysis of data collected through test items, it was seen improvement in students writing in post test than in pre-test. The students (Ss1-Ss10) were found using the words in an increased order and grammatically correct sentences in their writing in each test made and committed less grammatical errors in post test than in pre and progress test. Regarding mechanics of writing, their writing was found systematic in case of punctuation, proper use of paragraphs, in coherence and cohesion in writing. The peer correction and teacher correction technique was found productive in teaching writing through action research as a whole. Journal of NELTA, Vol. 17 No. 1-2, December 2012, Page 70-82 DOI: http://dx.doi.org/10.3126/nelta.v17i1-2.8094